Effect of methacholine induced bronchoconstriction on the pulmonary distribution and plasma pharmacokinetics of inhaled sodium cromoglycate in subjects with normal and hyperreactive airways. Issue 8 (August 1988) - Richards, R; Haas, A; Simpson, S; Britten, A; Renwick, A; Holgate, S
Abstract : Inhalation treatment may be less effective in the presence of bronchoconstriction because of the reduced penetration of drugs into the airways. The effect of bronchoconstriction on the lung deposition and plasma pharmacokinetics of inhaled sodium cromoglycate was examined. Ten subjects attended the laboratory on three occasions. On the first occasion a bronchial provocation test was performed to determine the concentration of methacholine required to reduce the forced expiratory volume in one second (FEV1) by 20% (PC20). On the two subsequent occasions subjects inhaled either saline or their PC20 methacholine, followed five minutes later by an aerosol containing sodium cromoglycate and stannous phytate labelled with technetium-99m. Twenty minutes later a gamma emission lung scan was performed to determine the intrathoracic deposition of the nebulised aerosol. The central:peripheral (C:P) ratio of lung deposition was then calculated. Measurements of FEV1 were made and blood samples taken for analysis of plasma sodium cromoglycate concentration at intervals for four hours. Methacholine led to a 23.4% (SEM 0.6%) lower FEV1 and a 2.8 times higher C:P ratio than those observed after saline. There was a direct correlation between log PC20 methacholine and the increase in the C:P ratio (r = 0.81). Despite these changes with methacholine, the plasma pharmacokinetics of inhaled sodium cromoglycate were not significantly different after methacholine and after saline, except that the maximum concentration achieved (Cmax) was increased. These observations suggest that the area of cromoglycate deposition and the anatomical site are less important in determining the plasma pharmacokinetics of cromoglycate than is the total dose delivered to the lung.